Reassessing the Role of State-Owned Enterprises in Central, Eastern and Southeastern Europe - Richmond, Christine (Departmental Papers; Departmental Paper, 2019)
The Central, Eastern, and South Eastern European (CESEE) region is ripe for a reassessment of the role of the state in economic activity. The rapid income convergence with Western Europe of the early 2000s was not always equally shared across society, and it has now slowed dramatically in many countries of the region.